Kendala Dan Cara Hakim Peradilan Tata Usaha Negara Pasca UU Administrasi Pemerintahan: Suatu Pendekatan Atas Penanganan Perkara Fiktif Positif - Wairocana, I Gusti Ngurah; Layang, I Wayan Bela Siki; Sudiarta, I Ketut; Martana, Putu Ade Hariestha; Sudiarawan, Kadek Agus; Hermanto, Bagus (Jurnal Hukum & Pembangunan, 2020)
After the enactment of the Law of Government Administration, had implied to shifting paradigm concerning the regime of Administrative Decision from negative fictive became positive fictive. However, the regulation into Law of Government Administration contains several obstacles on pratical scope towards Administrative Court Judges. Meanwhile enactment of Supreme Court regulation however Adiministrative Court Judges searching the suitable method after implication of positive fictive regime in the Administrative Procedural Law System. This study aims to analyze and discuss concerning obstacles and method by the Administrative Court Judges solving the practical obstacles after enactment of the Law of Government Administration. This study results is presented in a descriptive analysis paper.